Puffin book of stories for seven-year-olds - "Cooling, Wendy" (Puffin Books: London, 1996)
This entertaining assortment of stories from well-known children's authors will appeal to youngsters wanting to read independently and those who like to be read to. The collection includes contributions from Joan Aiken, Michael Rosen, Anita Desai, Geraldine McCaughrean and Ursula Moray Williams
Keywords: English fiction Short stories